2016
DOI: 10.3201/eid2212.160813
|View full text |Cite
|
Sign up to set email alerts
|

Highly Divergent Dengue Virus Type 2 in Traveler Returning from Borneo to Australia

Abstract: Dengue virus type 2 was isolated from a tourist who returned from Borneo to Australia. Phylogenetic analysis identified this virus as highly divergent and occupying a basal phylogenetic position relative to all known human and sylvatic dengue virus type 2 strains and the most divergent lineage not assigned to a new serotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Most recently, an extremely ancestral strain of DENV-2, QML22/2015, was isolated from an Australian tourist after returning home from Borneo. Interestingly, this isolate is ancestral to both sylvatic and human DENV-2 isolates, but more closely aligns with the sylvatic DENV-2 strains and did not react with non-sylvatic DENV-2 monoclonal antibodies [ 13 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, an extremely ancestral strain of DENV-2, QML22/2015, was isolated from an Australian tourist after returning home from Borneo. Interestingly, this isolate is ancestral to both sylvatic and human DENV-2 isolates, but more closely aligns with the sylvatic DENV-2 strains and did not react with non-sylvatic DENV-2 monoclonal antibodies [ 13 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Although this could be pure chance and if not, would possibly involve multiple factors, it could be interpreted as additional evidence that "sylvatic" behaviour may result in a lower evolutionary rate than an "urban" one. Overall, we need additional genetic and phenotypic data to properly determine whether there is a significant difference in evolutionary rate between sylvatic and non-sylvatic isolates of DENV and if an analogy can't reliably be drawn between sylvatic DENV and YFV [355,356]. Further investigating the impact of specific maintenance patterns on the evolutionary behaviour of YFV may allow us to gauge the changing landscape within its reach and thereby, the epidemic potential of this virus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this concern become more tangible after some studies have suggested human infection cases with presumably sylvatic DENV-2 strains. Phylogenetic analyses showed that the highly divergent strains (QML22/ 2015, D2Sab2015) of DENV-2 was basal and strikingly different from all other previously isolated strains (Liu et al, 2016;Pyke et al, 2017). In both cases, we excluded these sequences from our analyses, because including highly divergent sequences without knowing which genotype belong, may impact on the estimates for the whole dataset due to sampling bias and differences in the evolutionary rates.…”
Section: Discussionmentioning
confidence: 99%